Hamstring muscle elasticity differs in specialized high-performance athletes - Avrillon, S.; Lacourpaille, L.; Hug, F.; Le Sant, G.; Frey, A.; Nordez, A.; Guilhem, G. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The effect of training on hamstring flexibility has been widely assessed through the measurement of the maximal range of motion or passive torque. However, these global measures do not provide direct information on the passive muscle mechanical properties of individual muscle. This characterization is crucial to better understand the effect of interventions as selective adaptations may occur among synergist muscles. Taking advantage of shear wave elastography, we aimed to determine whether elite sport athletes exhibit different passive shear modulus of hamstring heads compared to controls. Passive shear modulus was measured on semitendinosus (ST), semimembranosus (SM), and biceps femoris (BF) using shear wave elastography with the knee flexed at 60° and 90°, and 90° of hip flexion. A total of 97 elite athletes from various sports including running sprint, figure skating, fencing, field hockey, taekwondo, basketball, and soccer and 12 controls were evaluated. The shear modulus measured at 60° of knee flexion was lower in SM for figure skating (P < .001; d = 1.8), taekwondo (P < .001; d = 2.1), fencing (P = .024; d = 1.0), and soccer (P = .011; d = 0.9) compared to controls, while no difference was found for athletic sprinters, field hockey, and basketball players. Shear modulus of the BF and ST muscle was not significantly different between controls and elite athletes, regardless of the sport specialization (all P values = 1). We provide evidence that the shear modulus of the SM is altered in athletes involved in elite sport practice performed over large range of motion and/or including substantial stretching program in training content (taekwondo, figure skating, fencing, and soccer).